2017
DOI: 10.1177/2399654417704664
|View full text |Cite
|
Sign up to set email alerts
|

Creating institutional preconditions for knowledge flows in cross-border regions

Abstract: Abstract:In recent years we have witnessed an intensive scholarly discussion about the limitations of traditional inward looking regional innovation strategies. New policy approaches put more emphasis on promoting the external connectedness of regions. However, the institutional preconditions for collaboration across borders have received little attention so far. The aim of this paper is to investigate both conceptually and empirically how policy network organizations can target the institutional underpinnings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…In turn, this may help quell suspicions over autonomist or separatist tendencies (Perkmann, 2000(Perkmann, , 2003(Perkmann, , 2005. Moreover, it would transmit the image of Euroregions as soft spaces and examples of institutional entrepreneurship for policy formulation and implementation scenarios (Miörner et al, 2018;Telle, 2017;Perkmann and Spicer, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this may help quell suspicions over autonomist or separatist tendencies (Perkmann, 2000(Perkmann, , 2003(Perkmann, , 2005. Moreover, it would transmit the image of Euroregions as soft spaces and examples of institutional entrepreneurship for policy formulation and implementation scenarios (Miörner et al, 2018;Telle, 2017;Perkmann and Spicer, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The tasks and purposes of a Euroregion. In their classification of the organisational activities of EU cross-border institutions, Miörner et al (2018) identified four different ranges of activities for policy-network organisations such as the Euroregions. These include i) the provision of information regarding the regulation of cross-border activities, the promotion of joint activities (i.e.…”
Section: The Euroregion: Definitions Activities Meaning and Classifmentioning
confidence: 99%
“…This means that the distance of social relations affects the content of innovation activities. Close social relations will strengthen trust between the innovators, reduce uncertainty and opportunism in cooperation, and reduce transaction costs in cooperation [43]. For the same reason, "nternalization" of cooperation is a best choice for cooperation between entities in the same organizational relationship [44].…”
Section: Proximities and Innovation Networkmentioning
confidence: 99%
“…The RIS model conceptualizes improvements to sparse innovation systems (what is referred to below as 'densification') by focusing on linkage-building processes (Tödtling & Trippl, 2005), and we specifically highlight the property of cross-border RIS (Lundquist & Trippl, 2013;Trippl, 2010) as potentially sparse innovation systems as where the border continually undermines interaction between innovators in various ways (Perkmann, 2007). Borders may hinder knowledge flows, labour mobility and access to critical resources (Cerina, Chessa, Pammolli, & Riccaboni, 2014;Miörner & Trippl, 2016;Miörner, Zukauskaite, Trippl, & Moodysson 2017) by raising the opportunity costs of cross-border interaction, channelling knowledge resource-search processes to remain within national boundaries, and reducing complementarities (Leick, 2012;Lundquist & Trippl, 2013).…”
Section: The Role Of Institutional Entrepreneurs In Upgrading Regionamentioning
confidence: 99%